2017
DOI: 10.1161/jaha.117.007026
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy Using Quadripolar Versus Non‐Quadripolar Left Ventricular Leads Programmed to Biventricular Pacing With Single‐Site Left Ventricular Pacing: Impact on Survival and Heart Failure Hospitalization

Abstract: BackgroundIn cardiac resynchronization therapy (CRT), quadripolar (QUAD) left ventricular (LV) leads are less prone to postoperative complications than non‐QUAD leads. Some studies have suggested better clinical outcomes.Methods and ResultsClinical events were assessed in 847 patients after CRT‐pacing or CRT‐defibrillation using either QUAD (n=287) or non‐QUAD (n=560), programmed to single‐site site LV pacing. Over a follow‐up period of 3.2 years (median [interquartile range, 1.90–5.0]), QUAD was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
1
26
2
Order By: Relevance
“…We sought to assess whether scar quantification by CMR is independently and incrementally predictive heart failure hospitalisation and death after CRT implantation when accounting for clinical data, the presence of LBBB and QRSd, and LV lead tip position in relation to scar19 and lead polarity 20 21…”
Section: Introductionmentioning
confidence: 99%
“…We sought to assess whether scar quantification by CMR is independently and incrementally predictive heart failure hospitalisation and death after CRT implantation when accounting for clinical data, the presence of LBBB and QRSd, and LV lead tip position in relation to scar19 and lead polarity 20 21…”
Section: Introductionmentioning
confidence: 99%
“…In addition to catheter ablation of AF, adjuvant therapies may also be considered. Recent advances in the field of cardiac resynchronization therapy like multipolar pacing have shown promising results reducing cardiac mortality, hospitalization rate, and AF burden …”
Section: Adjuvant and Future Therapies In Af And Hf Patientsmentioning
confidence: 99%
“…Recent advances in the field of cardiac resynchronization therapy like multipolar pacing have shown promising results reducing cardiac mortality, hospitalization rate, and AF burden. 46,47 In addition, catheter ablation results might be improved by novel therapies. Selectively targeting microRNAs might influence cardiac electrical and fibrotic remodeling after AF ablation.…”
Section: Adjuvant and Future Therapies In Af And Hf Patientsmentioning
confidence: 99%
“…A meta‐analysis of eight studies and a report with a large real‐world experience have shown that quadripolar leads have lower rates of implantation failure, postoperative lead dislodgement, revision, or deactivation. Clinical outcome in terms of mortality and heart failure hospitalization has also been shown to be reduced with quadripolar leads compared to bipolar leads in a nonrandomized but matched population . Manufacturers propose quadripolar leads of different diameters, shapes, and interlead spacing to address variations in coronary sinus (CS) tributary anatomy.…”
Section: Introductionmentioning
confidence: 99%